General practice funding underpins the persistence of the inverse care law: cross-sectional study in Scotland - McLean, Gary (Br J Gen Pract, 2015)
BACKGROUND: Universal access to health care, as provided in the NHS, does not ensure that patients’ needs are met. AIM: To explore the relationships between multimorbidity, general practice funding, and workload by deprivation in a national healthcare system. DESIGN AND SETTING: Cross-sectional study using routine data from 956 general practices in Scotland. METHOD: Estimated numbers of patients with multimorbidity, estimated numbers of consultations per 1000 patients, and payments to practices per patient are presented and analysed by deprivation decile at practice level. RESULTS: Levels of multimorbidity rose with practice deprivation. Practices in the most deprived decile had 38% more patients with multimorbidity compared with the least deprived (222.8 per 1000 patients versus 161.1; P<0.001) and over 120% more patients with combined mental–physical multimorbidity (113.0 per 1000 patients versus 51.5; P<0.001). Practices in the most deprived decile had 20% more consultations per annum compared with the least deprived (4616 versus 3846, P<0.001). There was no association between total practice funding and deprivation (Spearman ρ −0.09; P = 0.03). Although consultation rates increased with deprivation, the social gradients in multimorbidity were much steeper. There was no association between consultation rates and levels of funding. CONCLUSION: No evidence was found that general practice funding matches clinical need, as estimated by different definitions of multimorbidity. Consultation rates provide only a partial estimate of the work involved in addressing clinical needs and are poorly related to the prevalence of multimorbidity. In these circumstances, general practice is unlikely to mitigate health inequalities and may increase them.